History and Biography in Ancient Thought - Gentili, B. (Classical Studies - Book Archive pre-2000, 1988)
In this volume, the authors analyse ancient theories concerning the nature and the aims of historiography as well as biography. Such theories are investigated in their historical development, with special regard to the problem of oral communication in antiquity.